Validity and reliability of a commercially-available velocity and power testing device - Hannon, J. P.; Garrison, J. C.; Bothwell, J. M.; Esposito, P. E.; Jagim, A. R.; Jones, M. T.; Jennings, W.; Oliver, J. M. (Sports, 2018)
Given the relationship between explosive-type training and power adaptation, tracking movement velocity has become popular. However, unlike previous variables, tracking velocity necessitates the use of a valid and reliable tool to monitor adaptation over time. Therefore, the primary purpose of this research was to assess the validity and reliability of a commercially-available linear position transducer (LPT). Nine resistance-trained men completed four sessions consisting of a single set of barbell back squat to volitional failure at 75% or 90% one-repetition maximum. Kinetic and kinematic data were captured for each repetition by the LPT and a 3-dimensional motion capture system and bipedal force platforms. In total, 357 instances of data from both systems were analyzed using intraclass correlations (ICC), effect size estimates, and standard error of measurement. Overall, the LPT yielded excellent ICCs (all =0.94) and small/trivial differences (d < 0.60). When categorized by median values, ICCs remained high (all =0.89) and differences remained small or trivial with the exception of high peak velocities (d = -1.46). Together, these data indicate that the commercially-available LPT is a valid and reliable measure for kinetic and kinematic variables of interest with the exception of high peak velocities